2016
DOI: 10.1016/j.rbmo.2016.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Inositol as putative integrative treatment for PCOS

Abstract: Studies over the last decade have demonstrated that some polycystic ovary syndrome (PCOS) patients have abnormal insulin sensitivity (insulin resistance), independently from being overweight or obese. This induces the risk of developing type 2 diabetes in such PCOS patients. The use of insulin sensitizers (i.e. metformin), reduces such metabolic, and most hormonal, impairments. As metformin often induces side effects, new integrative strategies have been proposed to treat insulin resistance, such as the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 85 publications
(124 reference statements)
2
56
0
9
Order By: Relevance
“…Myo‐inositol promotes glucose uptake and FSH activity, while d ‐chiro‐inositol ameliorates insulin‐stimulated androgen synthesis in the ovary. Both of these effects may positively affect the ovarian function in PCOS . A number of studies have investigated possible clinical effects of inositol in PCOS, and in a systematic review including four randomized controlled trials and 100 patients, it was found that inositol treatment significantly increased the likelihood of spontaneous ovulation compared with placebo (risk ratio 2.32, 95% CI 1.14‐4.73) .…”
Section: Resultsmentioning
confidence: 99%
“…Myo‐inositol promotes glucose uptake and FSH activity, while d ‐chiro‐inositol ameliorates insulin‐stimulated androgen synthesis in the ovary. Both of these effects may positively affect the ovarian function in PCOS . A number of studies have investigated possible clinical effects of inositol in PCOS, and in a systematic review including four randomized controlled trials and 100 patients, it was found that inositol treatment significantly increased the likelihood of spontaneous ovulation compared with placebo (risk ratio 2.32, 95% CI 1.14‐4.73) .…”
Section: Resultsmentioning
confidence: 99%
“…The primary studies on inositol are too small, and existing reviews are narrative, without quantifiable estimates of effect on ovulation and live births . We aimed to undertake a systematic review to assess the effects of inositol on ovulation induction and reproductive outcomes, as well as on hormonal and glycaemic profile, when compared with placebo and/or metformin or clomiphene, in women with PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Таким образом, на основании многочисленных исследований высокую эффективность MИ при СПКЯ можно объяснить недостаточностью МИ, который является вторичным мессенджером внутриклеточного сигнала действия инсулина, ЛГ и ФСГ. При восполнении дефицита МИ повышается биодоступность вторичного мессенджера инсулина IPG, следовательно, улучшается внутриклеточный обмен, увеличиваются утилизация глюкозы, передача сигналов ЛГ и ФСГ [32,37,53,54]. Это указывает на то, что для правильного функционирования яичников важно поддерживать физиологическое соотношение МИ/ДХИ (40 : 1-100 : 1) [32,34].…”
Section: влияние инозитолов на клинико-лабораторные показатели больныunclassified
“…Инозитол и его 9 стереоизомеров представляют собой полиолы -сахарные спирты, которые ранее относили к семейству витамина В. Позже это положение было опровергнуто, так как около 75% суточной потребности инозитола продуцируется клетками организма из глюкозы [25,26].…”
unclassified